A revision of Begonia sect. Petermannia on Sumatra, Indonesia - Girmansyah, Deden; Susila, Susila; Hughes, Mark (Phytotaxa, 2019)
Begonia sect. Petermannia is revised for Sumatra, leading to the recognition of 14 species, nine of which are placed in a molecular phylogeny using nuclear ribosomal ITS data, showing they belong to two clades, intermixed with species from Java and Borneo. One new species is described, B. kemiriensis Girm & M.Hughes, from Gunung Kemiri, Aceh Province.